Isolation and characterization of azo-dye degrading microorganisms from a sequencing batch reactor set up - Vu, Ngoc Thuy (2008)
In this research, the possibility of decolorizing azo dye using bacteria isolated from a sequencing batch reactor was studied. Sample of sludge from the running SBR was taken and microbial isolation was carried out to obtain some bacteria. These isolated bacteria were inoculated in 2 media: Nutrient Broth with dye and Synthetic wastewater (C.I Reactive Red 141 and sucrose as carbon source) to investigate the color removal efficiency. C.I Reactive Red . 141 was used because it is one of typical dyes with persistent colors in the textile industry effluent discharges. Several studies aimed at determining the effects of various factors on this system, such as pH temperature, COD, concentration, and dye concentration were carried out. In another way, in order to achieve higher percentage of color removal when comparing with the efficiency of running SBR, finding the optimum pH, temperature, kinds of bacteria and dye concentration is needed. This study is also in line with the ultimate goal of achieving a high efficiency in treatment of azo dye using individual microbial isolates. Among 6 isolates, one showed the biggest decolorization with different concentration of dye within 24h at static condition and was initially identified as Bacillus sp. 35 deg.C is better than 25 deg.C or 45 deg.; pH 7.0-9.0, sucrose, as carbon source and 5% of seed culture.